Estado, poder e liberdade: Uma reflexão a partir dos culturalismos de Nelson Nogueira Saldanha e Joaquim Carlos Salgado - Layon Duarte Costa (2018)
The States (philosophical) History, in its self-revealing of the Spirit in search of its freedom, leads us to find that the current Constitutional Order (the Rule of Laws present phase) coalesces the juridical-political institutions conceived both in the Political Order (notably in ancient Greece), and in the Juridical Order (especially in classical Rome), since they are moments of the same historical-cultural-dialectical process. More than a simple juxtaposition of the institutes, ideas and values, the Constitutional Order creates them with new meanings, thus supplanting them in order to subordinate them to the new order, whose revealing characteristic is the conciliation between power and freedom. In order to give a philosophical sustenance to this work, the culturalist reflections proposed by Nelson Nogueira Saldanha (and his corresponding ideas about the classic exemplarities, man, History as suprasassumption of denials, culture, and forms of government) are chosen, as well as Joaquim Carlos Salgado (with the construction of the Escola Jusfilosófica Mineira, the idea of justice, the universal rights subject and the law as ethical maximum).